Overview of Pharmacological Therapies for Diffuse Tenosynovial Giant Cell Tumor - Antonia Stamatiou; Tu Nguyen-Ngoc; Laureline Wetterwald; Ana-Maria Dolcan; Giovanni Dei Tos; Stephane Cherix; Patrick Omoumi; Antonia Digklia (MDPI AG, 2023)
Tenosynovial giant cell tumor (TGCT) is a rare and locally aggressive benign tumor arising from the synovium of joints, bursae, and tendon sheaths. It is classified into localized (L-TGCT) and diffuse (D-TGCT) forms based on the extent of involvement. Surgical resection is the primary treatment, though achieving a definitive cure remains challenging due to the high recurrence rates, especially in D-TGCT. Systemic therapies targeting the CSF1-CSF1R axis have emerged as promising treatment options. CSF1R tyrosine kinase inhibitors (TKIs) such as imatinib, nilotinib, pexidartinib, and vimseltinib, alongside anti-CSF1R antibodies like emactuzumab, cabiralizumab, and lacnotuzumab, have shown encouraging results in managing TGCT, particularly when surgery is not feasible or poses significant morbidity. Other potential therapies, including local treatments and anti-inflammatory drugs, are being explored for TGCT management. This review provides an overview of systemic treatment options for D-TGCT, highlighting emerging therapeutic modalities and their potential implications. Effective management is crucial due to TGCT's significant morbidity despite its non-life-threatening nature, necessitating novel approaches to improve patient prognosis and quality of life.